Experimental investigations of extinguishing sodium pool fires using modified expandable graphite powders. (April 2022) - Zhang, Mei-Lin; Dong, Xi-Lin; Tang, Yan; Huang, An-Chi; Chen, Fang; Kang, Qing-Chun; Shu, Zhong-Jun; Xing, Zhi-Xiang
Abstract: A new type of composite fire-extinguishing powder was prepared with expandable graphite (EG) and sodium carbonate as the main materials. The morphology, structure, and thermal stability of the extinguishing powder were characterized. A fire-extinguishing experimental system was subsequently constructed to investigate the powder's fire-extinguishing performance for sodium fires. The results indicated that, compared with the unmodified EG, the modified EG had a 62.53% lower particle size and exhibited higher thermal stability. The fire control mechanism was also analyzed; the results revealed that sodium carbonate and EG exert a synergistic effect on flame suppression, and sodium carbonate improves fire-extinguishing efficiency.